Pengaruh Keteladanan Guru Dalam Menanamkan Nilai Akhlak Siswa Di Madrasah Tsanawiyah Negeri 2 Surakarta - Samae, Miss Saining; , Istanto, S.Pd.I., M.Pd (2017)
Teacher is the main role in guiding and developing children to reach the adultery. Teacher's preference is very influential for each students mentality, because teacher is a role model for students, therefore every act and behavior of teacher will be watched and be imitated. MTs Negeri 2 Surakarta is a school where students are not behaving according to syariat Islam. Whereas, teachers as the role models in the school, have been act nicely, such as wearing tidy uniform, doing polite things and obeying the rules. But in reality, there are still many students those have not followed the examples. So that, in this study the researcher will discuss about the influence of teacher as a role model in implanting student's moral values in MTs Negeri 2 Surakarta. In this study, the researcher formulated 2 problem statements, as follow: (1) what kind of exemplary behaviours do the teachers give in instilling moral values to the students of MTs Negeri 2 Surakarta?(2) what are the impacts? This study is aimed to know and describe the teachers‟ exemplary behaviours in instilling morals values to the students of Mts Negeri 2 Surakarta, and their impacts. This research is a field one by using qualitative approach, which has taken place at MTs Negeri 2 Surakarta. The subject of this research are the headmaster, the teachers, and the students of MTs Negeri 2 Surakarta. The methods used in collecting data are deep interview, observation, and documentation. The data are analyzed by using descriptive qualitative, thus data collected are cited ones. After that, the data collected are described in words. The results of this study conclude that the exemplary teachers in instilling moral values to students at MTs. Negeri 2 Surakarta are already good and influential. There are two forms of exemplary teachers in instilling moral values of students, namely words aspect and deed aspect. While the impacts of exemplary teachers toward instilling moral values of students have been influential and positive, since students already have akhlaqul karimah according to the teachings of Islam.